Risk of immune system and skin and subcutaneous tissue related adverse events associated with oxaliplatin combined with immune checkpoint inhibitors: a pharmacovigilance study - Zhang, Chunhong; Li, Furong; Dai, Ying; Zeng, Yifan; Yu, Xuben; Shi, Dawei (Frontiers in Pharmacology, 2024)
Background: Few studies have analysed oxaliplatin-induced adverse events (ADEs) in the immune system and skin and subcutaneous tissues through pharmacovigilance. We used this approach to analyse the risk of such ADEs when oxaliplatin combined with immune checkpoint inhibitors (ICIs).We evaluated the association between oxaliplatin and ADEs in the immune system and skin and subcutaneous tissues using the reporting odd ratio (ROR) for mining the ADE report signals in the FDA Adverse Event Reporting System database. Risk factors were analyzed using a binary logistic regression analysis using the sex and age of the patients.Results: There were 40,474 reports of oxaliplatin as primary suspect drug or second suspect drug.The signal intensities of ADEs such as type II hypersensitivity, type I hypersensitivity, type III immune complex-mediated reaction, anaphylactoid shock and cytokine release syndrome were high in PTs classified by SOC as immune system disorders; in the PTs classified as skin and subcutaneous tissue disorders by SOC, the signal intensities of ADEs such as skin toxicity, skin reaction, rash maculo-papular and skin fissures were higher. In the risk assessment between the two groups, rash showed an increased risk in the oxaliplatin-ICI group, with an OR of 1.96. Nivolumab in combination with oxaliplatin had an OR of 2.196 and an adjusted OR of 2.231. Combined with pembrolizumab, OR was 2.762 and the adjusted OR was 2.678.Type II hypersensitivity shows a stronger pharmacovigilance signal. Oxaliplatin in combination with nivolumab or pembrolizumab has been shown to increase the risk of rash.